Accumulation of heavy metals with the lichen thalli of Cladonia rangiferina L. at the roadside phytocenoses of the West Siberian Subarctic. (November 2019) - Popova, E
Abstract: The article reflects the results of a comparative analysis of the content and accumulation of heavy metals such as chromium, lead, nickel, zinc in the thalli of Cladonia rangiferina L. in the anthropogenic phytocenoses of the West Siberian Subarctic, Russia. The next series of accumulations of heavy metals in descending their concentrations in soils is Zn> Pb> Cr> Ni. Analysis of the results showed that among the factors affecting the accumulation of elements, the most significant wa the distance from the highway. The content of most elements is significantly (p <0.05) related. Cladonia rangiferina L. accumulates heavy metals depending on the location of the sampling point relative to the source of pollution. The coefficient of biological absorption, as well as the biogeochemical activity of the species, varies in different areas but has the greatest value in areas close to the source of anthropogenic load.